Natural convection heat transfer in façade integrated solar concentrators - Piratheepan, M; Anderson, T (Elsevier, 2015)
The use of facade (wall) integrated concentrating solar collectors is an area of developing interest within the field of energy-efficient building technology. One way of achieving such a device could be through the use of a static flat or parabolic reflector used in conjunction with a photovoltaic/thermal absorber and a vertical glazed aperture. However, to precisely predict the performance of such facade integrated collectors, it is essential to understand the heat losses from them. In general the thermal losses from these collectors can be calculated using existing relationships for flat plate solar collectors and fundamental heat transfer concepts. However there is no relationship in the literature to describe the natural convection heat transfer in the asymmetric enclosed air gap formed by a façade integrated concentrator as described. Hence, in this study, a relationship to describe the natural convection heat transfer in such enclosures was developed using an experimentally validated computational fluid dynamics analysis. The relationship shows that the heat transfer, expressed in terms on the Nusselt number, is strongly dependent on the Rayleigh number and the aspect ratio (A/H), and can be expressed in the form Nu = a Rab (A/H)c.
Keywords: Natural convection; Triangular enclosure; Façade; Solar concentrator